The value of ovarian hyperstimulation syndrome in predicting pregnancy outcome in women with polycystic ovarian syndrome and candidate for in vitro fertilization: A case-control study - Shamim Pilehvari; Nahid Radnia; Somayeh Ahmadiani; Elaheh Talebi-Ghane; Neda Alimohammadi; Zahra Mousaei Tokaldani (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Ovarian hyperstimulation syndrome (OHSS) as a known complication in women with polycystic ovarian syndrome (PCOS) may occur following inducible fertility treatments such as in vitro fertilization (IVF) and can affect the sequels of these treatments. Objective: This study aimed to assess the effects of OHSS on pregnancy outcomes through IVF in women with PCOS. Also, we assessed the value of baseline sexual hormones to predict the pregnancy's success. Materials and Methods: This case-control study was conducted on 180 consecutive women suffering from PCOS who were candidates for IVF at Fatemieh hospital in Hamadan, Iran, from May-July 2022. The women were assigned to the case group (with OHSS, n = 129) and the control group (without OHSS, n = 51). Measuring the sexual hormones was performed using the enzyme-linked immunosorbent technique. Results: In the multivariable logistic regression model, OHSS could not predict the likelihood of clinical or chemical pregnancy following IVF. None of the baseline sexual hormones could predict the successful chemical or clinical pregnancy in PCOS women following IVF. Conclusion: OHSS may not influence IVF-related outcomes in PCOS women. The values of sexual hormones may not also determine the pointed outcome.